CARBON FIBER REINFORCED POLYMER - THE FABRIC OF THE FUTURE? - Borchert, Marc; Bruns, Thilo; Hohendahl, Sabrina; Thoden, Bernd (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
This Article is about chances for carbon fiber reinforced polymers, following shortened CFRP, concerning its efficient, powerful, ecosensitive, sustainably and new technical inventions in several areas. It discusses this innovative new material concerning previous history, its production, its pros and cons and new possibilities, as well as the recycling in all its perspectives. Also, biodegradable alternatives of CFRP, like green composites and biocomposites are discussed.